Rational use of eculizumab in secondary atypical hemolytic uremic syndrome - Cordero, Lucía; Cavero, Teresa; Gutiérrez, Eduardo; Trujillo, Hernando; Sandino, Justo; Auñón, Pilar; Rivero, Marta; Morales, Enrique (Frontiers in Immunology, 2024)
BACKGROUND: Secondary atypical hemolytic uremic syndrome (secondary aHUS) is a heterogeneous group of thrombotic microangiopathies (TMA) associated with various underlying conditions. Unlike primary aHUS, there is still no hard evidence on the efficacy of complement blockade in secondary aHUS, since the two main series that investigated this subject showed discrepant results. Our work aims to reassess the efficacy of eculizumab in treating secondary aHUS. METHODS: Observational, retrospective, single-center study, in which we analyzed the hematological and renal evolution of 23 patients diagnosed with secondary aHUS who received treatment with eculizumab and compared them with a control cohort of 14 patients. Complete renal response was defined as the recovery of renal function before the event, partial renal response as a recovery of 50% of lost glomerular filtration rate, and hematological response as normalization of hemoglobin and platelets. RESULTS: We found no statistically significant differences in baseline characteristics or disease severity between both groups. After a median of 5 doses of eculizumab, the group of patients who received complement blockade presented a significant difference in renal response (complete in 52.3% of patients and partial in 23.8%) compared to the control cohort (complete response 14.3 % and partial of 14.3%). Rates of hematological remission were similar in both groups (90.9% in the eculizumab cohort and 85.7% in the control cohort). CONCLUSION: Early and short-term use of eculizumab in patients with secondary aHUS could be an effective and safe therapeutic option, assuring better renal recovery compared to patients who do not receive complement blockade.